Sustainable Agriculture Development in Northwest China Under the Impacts of Global Climate Change - Liu, Dachuan; Li, Yan; Wang, Pengfei; Zhong, Huaqi; Wang, Pu (Frontiers in Nutrition, 2021)
Northwest China has one of the most vulnerable agricultural systems in the context of global climate change. We argue that sustainable agriculture development in this region requires a systematic approach toward climate change adaptation, and propose a schematic framework for strategic thinking. We first briefly review the impacts of climate change on various agricultural environmental factors, including light, temperature, water, and atmosphere, and explores the effects of climate change on agricultural practices, such as disaster response, pests and weeds control, fertilizer application, and species selection. The study shows that climate change has increased extreme climate disasters such as drought and heat waves, and has expanded the scope and severity of pests and weeds, which in turn requires a series of changes in farming practices. These effects have profound impacts on farmland management, as well as the sustainability of the agricultural system. Based on the findings, the authors argue that the key adaptation strategies should include: (1) optimizing the geographic distribution of agriculture, (2) cultivating new crop varieties that can better adapt to the changing environment, (3) adjusting cropping timing and structure, (4) developing water-saving irrigation systems, (5) improving capacities of disaster prevention and mitigation at both household and government levels, and (6) strengthening the sciences, technology, and human resources to mitigate the adverse effects of climate change.